Haem disorder in modified myoglobins - Ahmad, Mansor; Kincaid, James R. (Portland Press, 1983)
Apomyoglobin was reconstituted with deuterohaem derivatives under various con-ditions. The fraction of disordered component, which is characterized by a 1800 rotation of the haem group, for the various preparations was determined by n.m.r. spectroscopy. By using the procedures described, it was shown that the fraction of disordered component is minimized if the reconstitution is carried out with high-spin ferric haem derivatives within an experimentally determined optimum pH range of 8-9.5. Use of low-spin derivatives in either the ferrous or erric forms leads to substantial increases in the fraction of disordered form. Attempted removal of the disordered form by selective oxidation and chromatographic purification was not effective.